Análise dos Indicadores de valor adicionado das empresas participantes do Índice de Sustentabilidade Empresarial (ISE) e das demais empresas listadas na BM& F Bovespa - Mazzioni, Sady (2013)
The aim of this paper is to compare the performance in generation and distribution of value added of companies belonging to the Corporate Sustainability Index (ISE) with other companies listed on the BM&FBovespa. A descriptive, documentary and quantitative research was carried out through a set of eleven indicators related to value added. The sample includes 143 companies in 2009, 182 in 2010 and 185 in 2011, respectively. Levene test and t test were used to verify if there were statistically meaningful differences between the indicators in the two groups of companies investigated. Results indicate that the companies belonging to ISE presented numbers consistently high, in the three studied periods, the average amount of value added generated. The findings showed that companies not belonging to ISE group offer better remuneration for the capital of third parties, while ISE companies pay more for equity.